Assessing the hazard of E-Cigarette flavor mixtures using zebrafish. (February 2020) - Holden, Laura L.; Truong, Lisa; Simonich, Michael T.; Tanguay, Robert L.
Abstract: Since 2007, electronic cigarette (e-cigarette) sales in the U.S. have surpassed those of tobacco cigarettes. This is due, in part, to manufacturer's claims that they are a safer alternative to tobacco cigarettes. However, formaldehyde, acrolein, and diacetyl have been detected in e-cigarettes and public knowledge of e-cigarette composition and ingredient bioactivity is conspicuously lacking. We evaluated the toxicity of nine e-cigarette flavor mixtures and their constituents in the developmental zebrafish, an excellent whole animal biosensor of chemical hazard. Seven of the nine flavors (78%) elicited adverse developmental responses at 1% by volume. The number of toxic endpoints varied greatly between flavors. Two flavors, Grape and Bubble Gum, had similar chemical compositions, but different toxicity profiles. We hypothesized that the toxicity was driven by a constituent present only in the Bubble Gum flavor, cinnamaldehyde. To replicate this toxicity, we built our own defined mixture. The addition of varying concentrations of cinnamaldehyde suggested that it drove the toxicity of these mixtures and that e-cigarette hazard can be flavor dependent. Highlights: 7 of 9 flavors tested in the developmental zebrafish model induced adverse responses at 1% by volume. Chemical composition and bioactivity varies by flavoring mixture. Developmental zebrafish is an excellent whole animal biosensor of chemical hazard.